A rare finding of Burkholderia pseudomallei isolate from neck abscess, 4 years after the last report in Makassar: a case report - Andi Meutiah Ilhamjaya; Munawir Muhammad; Ahmad Rahmat Ramadhan; Rizalinda Sjahril (Journal of Clinical Microbiology and Infectious Diseases, 2021)
Introduction: Burkholderia pseudomallei is the causative agent of melioidosis, known as Whitmore's disease, a tropical disease in humans. The bacteria can infect humans or animals, mostly found in contaminated water and soil. It spreads by direct contact with contaminated sources, inhalation or ingestion of contaminated dust or water droplets, or contact with soil through skin abrasions. Melioidosis is highly endemic in Southeast Asia and Northern Australia but rare in Makassar. Case description: A 44-year-old woman shows a red mass on the right neck, reddish, palpable, ±6x5x4mm in size, and is soft in consistency and has a cystic impression. Direct gram showed purulent mixed with blood. 24 hours after incubation under aerobic conditions, grew small colonies, smooth, cream in color, non-lactose fermenter on Mac Conkey agar. Indirect gram shows a small, gram-negative rod (safety pins appearance). The colonies were positive in the catalase and oxidase test, with citrate and urease test was negative. Burkholderia pseudomallei was identified by Vitek2 with 97% Probability. It was susceptible to doxycycline, ceftazidime, and Trimethoprim/Sulfamethoxazole. Conclusion: This is a rare finding in a clinical isolate found in Makassar. A newly emerged case, four years after the last report in Makassar. This is still a challenge to public health problems in Makassar, must be reported consistently and never lost to follow up to get proper treatment.